General Relativistic Behaviour of a Test Particle and Doppler’s Effect in a Model: Exploring the General Relativistic Behavior of Test Particles and Doppler's Effect in a Model (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper provides the behaviour of a test particle and Doppler’s effect by considering suitable model.